Optimizing the Role of Zakat, Infaq, Sedekah, and Waqf (ZISWAF) in Poverty Alleviation in Indonesia - Siti Nuraini (PT. Berkah Smart Academica, 2025)
This research is motivated by the paradox of persistent poverty in Indonesia despite the country's status as one of the most generous nations with vast Islamic philanthropy potential. The core problem lies in the suboptimal management of Zakat, Infaq, Sedekah, and Waqf (ZISWAF), which is still dominated by charity-consumptive patterns and low institutional transparency. This study aims to analyze the optimization strategies of ZISWAF through the transformation of productive empowerment models and digital technology integration to achieve sustainable poverty alleviation. The method employed is a Systematic Literature Review (SLR) using the PRISMA protocol on 25 reputable journal articles from Scopus and Sinta databases (2021-2025). Research data indicates that the adoption of FinTech and hybrid instrument innovations, such as Cash Waqf Linked Sukuk (CWLS), significantly enhances accountability and fund collection volumes. The findings conclude that ZISWAF optimization requires synergy between professional management (Amil), tax regulation legality, and a shift in distribution paradigms toward human capital investment. The final conclusion emphasizes that integrating the digital ecosystem and strengthening the economic resilience of Mustahik through intensive mentoring are key to transforming Islamic philanthropy into a social fiscal force capable of permanently breaking the chain of structural poverty in Indonesia.